PENGARUH TETRASIKLIN TERHADAP KERENTANAN OLEH SERANGAN PENYAKIT MAS, PERTUMBUHAN DAN DAYA TETAS TELUR LELE DUMBO (Clarias gariepinus)EFFECTS OF TETRACYCLINE TO SUSCEPTIBILITYAGAINST MAS, GROWTH RATE AND HATCHING RATE OF - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTACT: Study was conducted to find out the effect of tetracycline medication to susceptibility against MAS, growth rate and hatching rate of African catfish (Clarias gariepinus). The results indicated that intraperitoneal injection of tetracycline (50 mg/kg fish) could decrease the growth rate of fish significantly (P